Pengelolaan Limbah Infeksius Rumah Tangga pada masa Pandemi COVID-19 - Astry Axmalia; Rendi Ariyanto Sinanto (Jurnal Kesehatan Komunitas, 2021)
Handling infectious waste is a major global concern for public health and the environment if improperly hands. Personal protective equipment used masks, gloves are the main contribution to the volume of waste.Â The purpose of this literature study is to discuss ways of handling infectious waste, household at the time of a pandemic COVID-19. The method used is a literature review. Literature in the form of national journals published from 2020 until 2021. The collection of literature using google scholar and http://garuda.ristekbrin.go.id/ database with the keywords "infectious waste COVID-19", "impact COVID-19", and "infectious waste householdâ€. The search results obtained 21 articles according to keywords. Once filtered using exclusion and inclusion criteria obtained 8 articles in the review. The results of the reviews indicate the amount of medical waste during a pandemic COVID B3-19 increased, this infectious waste is classified as medical waste garbage hazardous and toxic materials or B3, medical waste originating from households and waste from health care facilities, the public has not fully known and yet do the processing infectious waste, household, then the lack of information regarding the effectiveness of the handling of infectious waste COVID-19.Â It is hoped that the health facilities and the community will be able to carry out burial procedures by Permenlhk Number P.56/Menlhk-Setjen/2015 concerning Procedures and Technical Requirements for Management of Toxic Hazardous Waste from Health Service Facilities and circular No. SE/MENLHK/PSLB3/3/2020 concerning Management of Infectious Waste (B3 Waste) and Household Waste from Handling Corona Virus Disease (COVID-19).